2000
DOI: 10.1272/jnms.67.186
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Occupational Low Back Pain in Truck Drivers.

Abstract: The factors in volved in occupational low back pain occurring in professional drivers were investigated epidemiologically with questionnaires (92 items) including low back symptoms, personal factors and occupational factors. The responses of one hundred fifty-three of one hundred eighty-one truck drivers who work in a large chemical industry corporation were analyzed after they had completely filled in questionnaires. As analysis of the results shows, the prevalence of LBP in one month of the survey was 50.3%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 7 publications
1
33
0
6
Order By: Relevance
“…Four out of six studies showed a moderate positive association (average OR=2.1) between sitting and LBP [7,9,22,44]. The remaining two studies found an almost null association between professional driving and LBP [6,53].…”
Section: Lbpmentioning
confidence: 90%
See 2 more Smart Citations
“…Four out of six studies showed a moderate positive association (average OR=2.1) between sitting and LBP [7,9,22,44]. The remaining two studies found an almost null association between professional driving and LBP [6,53].…”
Section: Lbpmentioning
confidence: 90%
“…However, almost half the OR's factored in were not significant, weakening the supposed effect of sitting [6,20,36,37,39,41,43,53,62,76].…”
Section: Lbpmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Low back pain corresponds to over 50% of all musculoskeletal dysfunctions that cause chronic disabilities in industrialized countries, leading to expenses with treatments and absenteeism from work. 5,[7][8][9][10][11][12][13] Low back pain or lumbar pain runs between the lower ribs and the glutei and can be related to multiple causes such as neoplasias; inflammatory and infectious diseases; systemic bone alterations; congenital abnormalities; degenerative, visceral, and psychogenic diseases; traumas; and mechanical causes. 4,14 Occupational low back pain is related to the latter cause; the onset occurs while the individual is exerting occupational activities and therefore is related to certain working situations such as maintenance of the same posture for prolonged periods, repetitive movements, lifting of heavy objects, and tilting and torsion of the trunk.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 Occupational low back pain is related to the latter cause; the onset occurs while the individual is exerting occupational activities and therefore is related to certain working situations such as maintenance of the same posture for prolonged periods, repetitive movements, lifting of heavy objects, and tilting and torsion of the trunk. 7,11,15,16 Moreover, not only can the exposure to risk factors lead to the onset of low back pain, but also the time of exposure to such factors can be a determinant of onset of low back pain.…”
Section: Introductionmentioning
confidence: 99%